Proximate composition and energy density in relation to Argentine hake females (Merluccius hubbsi) morphometrics and condition indices - Leonarduzzi, Ezequiel (2014)
Argentine hake is the most important economic demersal resource for the fisheries of the South-West Atlantic Ocean. Nevertheless, not many studies on its bioenergetic dynamic have been reported. Proximate composition and energy density were analyzed in muscle, liver and gonads and they were related to maternal morphometrics (length and gutted weight) and condition factor (K), gonadosomatic index (GSI) and hepatosomatic index (HSI). Argentine hake females were collected during the beginning of their reproductive season in the main spawning ground reported for this species. The results support the idea that muscle represents the main deposit of proteins and the liver is the main deposit of lipids. Furthermore, it was observed that females with higher content of lipid in their liver had also greater lipid reserves in muscle. All hake females reached the same proportion of lipid and protein reserves in their gonads independently of lipid and protein stored in their liver. Water content reflected the lipid content on muscle, liver and gonad. Lipid content in the three tissues was positively related to maternal morphometrics. Being a good indicator of the physiological condition of hake female the HSI was the only variable that reflected changes in lipid content and energy density.